2009
DOI: 10.1186/1742-4690-6-55
|View full text |Cite
|
Sign up to set email alerts
|

96 shRNAs designed for maximal coverage of HIV-1 variants

Abstract: Background: The RNA interference (RNAi) pathway is a mechanism of gene-suppression with potential gene therapy applications for treating viral disease such as HIV-1. The most suitable inducer of RNAi for this application is short hairpin RNA (shRNA) although it is limited to suppressing a single target. A successful anti-HIV-1 therapy will require combinations of multiple highly active, highly conserved shRNAs to adequately counter the emergence of resistant strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 49 publications
1
46
0
Order By: Relevance
“…5c). The loop sequence followed a previously described format of 8 nt, where the nucleotide N is complementary to the target site (45). Contrasting results for siRNAs (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…5c). The loop sequence followed a previously described format of 8 nt, where the nucleotide N is complementary to the target site (45). Contrasting results for siRNAs (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Meanwhile, molecular research of HIV infection in MSM is also needed. RNAi technology is a powerful tool to silence target gene expression in vitro and in vivo [27,11], and has been successfully used as an effective approach to inhibit the HIV replication [17,29,35]. The use of RNAi to inhibit HIV-1 represents a novel and potentially powerful antiviral strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, RNAi has been exploited in gene therapy strategies for HIV-1 [9,24,33]. It has been reported that about 200 published siRNAs and shRNAs are tested against HIV-1 [17], most of HIV genes and regular sequences are successfully targeted for RNAi [1,10,16].…”
Section: Introductionmentioning
confidence: 99%
“…Wt-(Wild type) Virions, Viruses, Proviruses, transcript et cetera will be used to indicate respectively infective HIV Virions, Viruses, Proviruses, transcript et cetera that can be found in the population. The shRNA sequences transducted by H-Vectors and related siRNAs are to be designed to target specific wt-HIV genes and transcripts, such as Gag, Pol, Env or Tat, Rev and Nef genes and their transcripts; a very good review about possible shRNAs with these characteristics can be found in Mcintyre et al [15]. Specifically, it seems that the early transcribed Tat, Rev and Nef genes [16] could be good candidates to be used to interfere with HIV infection [17].…”
Section: The Hypothesismentioning
confidence: 99%